Synthesis of comb-type block copolymers by grafting through method: electrical properties and determination of activation energy via conductivity - Pihtili, Guzin; Demirelli, Kadir (Taylor & Francis Inc, 2020)
Poly[epsilon-CL-b-(MMA-comb-EMA)]comb-type polymers were synthesized by ATRP and epsilon-caprolactone macroinitiator and macromonomer. Methyl methacrylate macromonomer was synthesized from acylation reaction of methacryloyl chloride with PMMA ended 7-hydroxy coumarin. The macroinitiator was prepared from the reaction of chlorine acetyl chloride P(epsilon-CL). The synthesized polymers were characterized by FT-IR, H-1-NMR and C-13-NMR techniques. The average molecular weight and molecular weight distribution of polymers were measured by GPC method. Thermal properties of samples were studied by DSC/TGA techniques. Dielectric and Ac conductivity measurements were performed. Dielectric constant (epsilon'), dielectric loss factor (epsilon|) and conductivity behaviors of comb-type polymer were measured at room temperature between the frequency of 100-2000 Hz and over the temperature range 303-413 K at 1 kHz reported as compared with each other. Besides, their effects on the electrical properties by doping with EuCl3 for some of the comb copolymers were and were investigated. The activation energy (E-a) was calculated from conductivity. We reported it was determined that the (epsilon') and (epsilon|) values decreased with increasing frequency. There are also many application areas for comb polymers for example; nanotechnology, medicine. The aim of this study is to synthesize comb-type copolymers in different compositions and to investigate their electrical properties.
Keywords: Activation energy; comb-type polymer; dielectric properties; Europium (III) chloride; methyl methacrylate macromonomer